Future-Proofing Geriatric Mental Health Care Services in India: Training and Policy Directions. Issue 5 (September 2021) - Philip, Sharad; Gajera, Gopi; Nirisha, P Lakshmi; Sivakumar, Palanimuthu Thangaraju; Barikar, Malathesh C.; Panday, Praveen; Patley, Rahul; Chander, Rakesh; Sinha, Preeti; Basavarajappa, Chethan; Manjunatha, Narayana; Kumar, Channaveerachari Naveen; et al.
Background: A burgeoning rise in the elderly subpopulation is being noted in India. This rise has already earned the designation as a shining nation by the United Nations/World Health Organization. This growth will take the elderly subpopulation to 324 million persons above 60 years by 2050. The mental health needs of this subpopulation are varied and nuanced compared to that of the general population. The risk and prevalence of mental health morbidity are also greater. There is an urgent need to gear up the health care systems. Considerations: Various aspects of the ongoing demographic transitions are considered alongside available health information. Legislative mandates and laws are also reviewed to provide context to qualify the action points and recommendations. Recommendations, India must act urgently to strengthen health care delivery systems in a concurrent multipronged approach. These efforts should focus on developing trained Human Resources and adequate infrastructural resources. Review mechanisms to inform on required updates on best practices and evidence-based medicine must also be incorporated and developed to perform periodically.